MAKNA FILOSOFIS UPACARA METATAH DALAM LONTAR EKA PRATHAMA - I Wayan Titra Gunawijaya; Astu Arya Putra (Sekolah Tinggi Agama Hindu Negeri Mpu Kuturan Singaraja, 2019)
The implementation of the Yajna ceremony in Bali is arranged in a variety of literary sources, one of which is Lontar as a source of knowledge in carrying out religious rituals. Eka Prathama ejection is one of the yajna ejection used as a guide for the implementation of religious rituals of the Balinese Hindu community. The ethics of conducting metatah rituals is especially important to observe in order to create rituals that truly contain the concept of yajna, namely writing and sincerity. In addition the use of banten is also explained in Eka Prathama ejection, as well as the meaning of banten used.